2022
DOI: 10.3389/fnagi.2022.761053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exergaming-Based Tai Chi on Cognitive Function and Dual-Task Gait Performance in Older Adults With Mild Cognitive Impairment: A Randomized Control Trial

Abstract: BackgroundDeclined cognitive function interferes with dual-task walking ability and may result in falls in older adults with mild cognitive impairment (MCI). The mind-body exercise, Tai Chi (TC), improves cognition and dual-task ability. Exergaming is low-cost, safe, highly scalable, and feasible. Whether the effects of exergaming-based TC is beneficial than traditional TC has not been investigated yet.ObjectivesThe objective of this study was to investigate effects of exergaming-based TC on cognitive function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 45 publications
5
55
0
Order By: Relevance
“…At the follow-up assessment, the Baduanjin group improved in both cognitive and motor dual-task performance. Previous research reported that mind-body exercise, such Tai Chi, might have a positive effect on dual-task performance in older adults (62)(63)(64). In line with previous research on older adults, our study revealed that Baduanjin might improve dual-task performance in middle-aged patients with schizophrenia.…”
Section: Discussionsupporting
confidence: 91%
“…At the follow-up assessment, the Baduanjin group improved in both cognitive and motor dual-task performance. Previous research reported that mind-body exercise, such Tai Chi, might have a positive effect on dual-task performance in older adults (62)(63)(64). In line with previous research on older adults, our study revealed that Baduanjin might improve dual-task performance in middle-aged patients with schizophrenia.…”
Section: Discussionsupporting
confidence: 91%
“…Apart from studies in the meta-analysis, an individual trial showed that 6 months of 10-form Tai Chi training (three times per week) was effective in improving the mental switching component of executive function in older adults with amnestic MCI (Sungkarat et al, 2018 ). The beneficial effects on executive function in exergaming-based Tai Chi group (modified Yang style), traditional Tai Chi group (simplified 24-form Yang style), and untrained controls were compared (Liu et al, 2022 ). During the Tai Chi exergames, participants imitated a virtually-presented Tai Chi instructor and made real-time adjustments in response to immediate feedback.…”
Section: Amelioration Of the Clinical Symptoms Of MCI Through Tai Chi...mentioning
confidence: 99%
“…In addition to field training, the effects of Tai Chi online courses on the risk of falls have been explored during the COVID-19 pandemic. Liu et al ( 2022 ) found that the exergaming-based Yang-style Tai Chi and traditional Yang-style Tai Chi groups had comparable improvements in gait performance and cognitive-dual-task cost, both of which were better than those of the untrained control group. Inconsistently, Li et al ( 2021 ) found that though the home-based Tai Chi group performed better on tests of balance, chair stands, and gait performance than the stretching group, no significant reduction in falls (incidence rate ratio: 0.58; 95% CI: 0.32, 1.03) was observed possibly because of the small sample size ( N = 15 for each group).…”
Section: Amelioration Of the Clinical Symptoms Of MCI Through Tai Chi...mentioning
confidence: 99%
“…A total of 10 studies (9,22,23,(25)(26)(27)(28)(29)(30)(31) with 591 patients assessed the Montreal Cognitive Assessment scores after treatment. High significant heterogeneity was found among these studies (I 2 = 83%), after heterogeneity tests we find that an article is a source of heterogeneity (30), heterogeneity was reduced after remove this article (I 2 = 14%), then fixed-effects model was used. The results showed that the impact of TCEs on cognitive function (MoCA) in elderly with cognitive impairment is statistically significant [MD = 2.50, 95% CI (2.03, 2.97), p < 0.00001].…”
Section: Primary Outcome-global Cognitive Functionmentioning
confidence: 99%